2021
DOI: 10.3389/fendo.2021.619586
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Sodium-Glucose Transporter 2 Inhibitors on Atrial Fibrillation and Atrial Flutter: A Systematic Review and Meta- Analysis of Randomized Placebo-Controlled Trials

Abstract: BackgroundHyperglycemia is associated with an increased risk of developing atrial fibrillation (AF) and atrial flutter (AFL). Sodium-glucose transporter 2 inhibitors (SGLT2i) have been reported to prevent AF/AFL in some studies, but not others. Therefore, a meta-analysis was performed to investigate whether SGLT2i use is associated with lower risks of AF/AFL.MethodsPubMed, Scopus, Web of Science, Cochrane library databases were searched for randomized placebo-controlled trials comparing SGLT2i and placebo.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 59 publications
1
35
0
Order By: Relevance
“…First, SGLT2is were observed in this meta‐analysis with the lower risks of atrial fibrillation, hypertension, bradycardia, hypertensive emergency, cardiac failure, cardiac failure chronic, cardiac failure acute and cardiac failure congestive. Similarly, the efficacy of SGLT2is in reducing the incidence of atrial fibrillation and the protective efficacy against hypertension was observed in previous studies 26–29 . Meanwhile, three heart failure trials 8–10 of SGLT2is have definitely demonstrated the anti‐heart failure effect of this drug class.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…First, SGLT2is were observed in this meta‐analysis with the lower risks of atrial fibrillation, hypertension, bradycardia, hypertensive emergency, cardiac failure, cardiac failure chronic, cardiac failure acute and cardiac failure congestive. Similarly, the efficacy of SGLT2is in reducing the incidence of atrial fibrillation and the protective efficacy against hypertension was observed in previous studies 26–29 . Meanwhile, three heart failure trials 8–10 of SGLT2is have definitely demonstrated the anti‐heart failure effect of this drug class.…”
Section: Resultssupporting
confidence: 59%
“…Similarly, the efficacy of SGLT2is in reducing the incidence of atrial fibrillation and the protective efficacy against hypertension was observed in previous studies. [26][27][28][29] Meanwhile, three heart failure trials 8-10 of SGLT2is have definitely demonstrated the anti-heart failure effect of this drug class. Thus, compared to GLP1RAs and DPP4is SGLT2is are more suitable for patients at high risk of hypertensive emergency, heart failure, atrial fibrillation or bradycardia.…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…Compared with 3 meta-analyses [30][31][32] that showed SGLT2 inhibitors with a decreased risk of atrial fibrillation, this meta-analysis additionally identified both high-and lowdose SGLT2 inhibitors with a decreased risk of bradycardia. This may suggest the antiarrhythmic effects of SGLT2 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Three previous meta-analyses ( Li et al, 2021a ; Li et al, 2021b ; Zhou et al, 2021 ) identified SGLT2is with the reduced risk of atrial fibrillation, whereas they failed to explore the association between SGLT2is and bradycardia. Our meta-analysis further revealed the association between use of SGLT2is and a lower risk of bradycardia besides that of atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%